Taxonomy of ’Euconnus complex’. Part XI. Status of Euconophron and Scopophus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Euconophron was described over a century ago and includes over 120 nominal species, being the third largest subgenus of Euconnus. However, its diagnosis remains unclear. Western Palaearctic species seem to form a homogenous group characterized by emarginate or bifurcate aedeagal apex, whereas exotic members of this subgenus show a great diversity in external and genital characters. Moreover, Scopophus, a Nearctic subgenus of Euconnus, and at least some species placed in Euconnus s. str. outside Europe seem to be very similar to Euconophron. In the present paper the status of Euconophron and Scopophus is verified on the basis of morphological structures of their type species, i.e., Scydmaenus promptus Coquerel (the type species of Euconophron) and Euconnus affinis Casey (the type species of Scopophus), each represented by respective type specimens. It is concluded that: i) the redescription of Scydmaenus promptus published by H. Franz was based on a misidentified specimen; ii) Euconophron can be maintained as a separate subgenus if unique characters of western Palaearctic species are included in its diagnosis; iii) Scopophus is a junior synonym of Euconnus s. str.; iv) status of species currently placed in Euconophron that occur outside western Palaearctic seems dubious, some of them may belong in Euconnus s. str. (this problem requires further study and species redescriptions); v) Euconnus s. str. and Euconophron may be closely related. Emended diagnosis of Euconophron is given, and lectotypes are designated for Scydmaenus promptus and Euconnus affinis.